Registro de marca : estudo do uso do sistema marcário por empresas sergipanas - Medeiros Filho, Adonis Reis (2014)
Used long time, trademarks have fundamental paper to designate provenance of products or manufacturers, in addition to having vast importance in relations between companies and consumers because they act as a safety factor for both, facilitating the identification of products and companies. In Brazil, obtained regulation from the Decree 2682 of 1875, and are currently regulated by Law nº 9279 of May 14, 1996, his registration is held by the INPI, and comes to be considered the most important among the intellectual properties. The objectives of this study are to evaluate whether the companies from Sergipe promote the protection of their trademarks through registration and investigate the use of the registry gives satisfactorily or not, in order to perform a state panorama related to trademark registration for that is subsequently possible to trace actions and objectives to promote the culture of protection of trademarks. The sample searched was 761 companies from Sergipe, subdivided into 5 groups of classes of activities, named according to their relationship with their branches and denominated as follows: Construction, Foods, Confection and Graphic Services and the remaining are grouped in a class called Other Activities, with branches ratings less significant occurrences. Data were collected from consultations in the systems of Federal Revenue Department and the INPI, and data analysis was performed using a quantitative approach, showing that only 8.94% of the surveyed companies made filing applications for trademark registrations. Data were collected from consultations in the systems of Federal Revenue Department and the INPI, and data analysis was performed using a quantitative approach, showing that only 8.94% of the surveyed companies made filing applications for trademark registrations, where 31,97% are registered, the same 31.97% are filed or extinct and the others in progress. Also showing an average of 8.62 years for the application to be made by the companies, counted from the year they were open, the prevalence of applications of trademarks of products, the branch of Construction with the worst numbers among business segments and Individual Entrepreneurs with worse outcomes between the legal natures of the companies analyzed.